‘Spaces of drink’ and contemporary rural culture: exploring a Midland village - Wright, Wilfred (2024)
Within the wider ecosystem of public social spaces, how varied drinking spaces in rural areas act to facilitate the identities of local communities is of great interest to both rural geographers and those engaged in studying the geography of drink. Such spaces are key to analyse, given the reported centrality of such establishments in facilitating sense of place, especially in more peripheral communities. This research attempts to adds contemporary relevance to the ideas explored by the likes of Bowler and Everitt (1999) and Maye, et al. (2005), surrounding the differing ‘cultural terrain’ present in differing drinking spaces, and how those differences interact to create individual identities and appreciations of local place. Through a process of interviews, focus groups, participant observations and incursions into the archives of the local history society, an ethnographic understanding of one specific large village in the rural East Midlands could be appreciated. The conclusions of the thesis highlight how, despite processes of economic rationalisation and increasing social isolation, spaces of drink continue to play a significant role in rural communities.